Don’t believe the hype. AI myths and the need for a critical approach in higher education (Journal of Applied Learning and Teaching, 2025)
Our editorial critically interrogates the pervasive hype surrounding artificial intelligence (AI) and generative artificial intelligence (GAI) in higher education, dismantling eight entrenched myths that shape current discourse. We demonstrate that AI is not an inherently autonomous, intelligent, or objective entity but rather a product of human ingenuity, dependent on vast and often exploitative labour and data extraction practices. Contrary to claims that AI will automatically engender a more democratic, equal, and sustainable world, our analysis reveals that these technologies tend to exacerbate existing inequalities, environmental degradation, and labour precarity. Moreover, the belief that the United States exclusively dominates the AI arena is challenged by the rapid ascent of China. We also question the notion that AI will have a negligible impact on the job market, arguing instead that automation driven by GAI is reshaping work and deepening economic disparities.In higher education, the purported revolution promised by Silicon Valley is undermined by its detrimental effects on academic integrity and the erosion of evidence-based pedagogical practices, compounded by the prevailing crisis of higher education. We contend that, amid this complex landscape, a critical re-evaluation of AI’s role is imperative. We call upon intellectuals in higher education to lead a transformative agenda—embedding critical AI literacy into curricula and institutional practices—to ensure that AI serves as a tool for enhancing human insight and social justice rather than perpetuating technological illusions.